2017
DOI: 10.22260/isarc2017/0091
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Robotic System with Tunnel Inspection Tool Positioning

Abstract: An overview of the fundamental aspects of the project architecture and design will be detailed. In addition, the developed and implemented algorithm for positioning the Tunnel Inspection Tool on detected cracks shall be presented. Finally, experimental evidence to validate the functionality of the ROBO-SPECT system in a real motorway tunnel with ongoing traffic will be provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…On the other hand, to reduce accidents related fall of person from height or struck by moving or stationary objects, the adaptation of robotics is an effective safety strategy that is being used recently, Therefore, in Hong Kong construction industry, the robotics in the construction industry could play an important role. Recent studies [55][56][57][58] indicated that the robotic can do a number of different forms of work in the construction industry including excavation, demolition buildings, tunnel inspection and constructing walls, etc. as shown in Figure 4.…”
Section: Advance Technologies For Safety Enhancementmentioning
confidence: 99%
“…On the other hand, to reduce accidents related fall of person from height or struck by moving or stationary objects, the adaptation of robotics is an effective safety strategy that is being used recently, Therefore, in Hong Kong construction industry, the robotics in the construction industry could play an important role. Recent studies [55][56][57][58] indicated that the robotic can do a number of different forms of work in the construction industry including excavation, demolition buildings, tunnel inspection and constructing walls, etc. as shown in Figure 4.…”
Section: Advance Technologies For Safety Enhancementmentioning
confidence: 99%
“…Naturally, heavy-duty operations have been tackled, like for instance façade installation [6,7,8], forestry [9], mining [10] and generic earthworks [11,12]. Several solutions have also been developed in order to facilitate inspection of buildings and infrastructures [13,14,15]. Finally, in accordance with the trends that will be introduced in the following sections, more recent contributions tackled novel application contexts like for instance realization of wooden buildings [16], interior and exterior renovation [17,18,19,20], additive manufacturing [21,22] and also decommissioning of nuclear power plants [23,24].…”
Section: Introductionmentioning
confidence: 99%